Effectivity of Pregnancy Paper Fan and Android Notification System Toward Knowledge, Attitude, and Adherence of Pregnant Women on Iron Supplements Consumption - Armi, Widdefrita; Novelasari; Rahmiati, Eka; Audia Nadira, Nindy (Universitas Airlangga, 2023)
Background: Anemia during pregnancy is a kind of problem that most expectant mothers are dealing with. Consuming iron supplements is one kind of solution to lower the cases of anemia. However, the number of anemia in expectant mothers in West Sumatra is still high, 43% of them experience anemia in pregnancy and 52% of them did not adhere to consuming iron supplements. Purpose: Creating two kinds of media to motivate expectant mothers in consuming iron supplements, which are pregnancy paper fan and an Android notification system installed on their mobile phones, as well as to determine the effectivity of both media on knowledge, attitude, and adherence on consuming iron supplements. Methods: The population of this research is expectant mothers with a number of sample 110 respondents, where 55 respondents were intervened with pregnancy paper fan and 55 respondents were intervened by an android notification system. Results: The result of the bivariate analysis shows that the Android notification system has a significant impact on the adherence, knowledge, and attitude of expectant mothers on consuming iron supplements during pregnancy. However, the pregnancy paper fan has a significant impact only on knowledge and the adherence of expectant mothers on consuming iron supplements, while there is no significant impact on attitude toward consuming iron supplements. Conclusion: The use of the Android Notification System is effective on knowledge, attitudes, and compliance of expectant mothers on consuming iron supplements.